Would MERCOSUR's exports to the EU profit from trade liberalisation? Some general insights and a simulation study for Argentina - Felicitas Nowak-Lehmann D.; Inmaculada Martínez-Zarzoso (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2003)
In this study, MERCOSURś past exports to the EU under the protectionist environment of the period between 1988 and 1996 are examined and an attempt is made to determine MERCOSURś exportsǵrowth potential in a liberalised EU market. A sectoral study is considered indispensable since tariff and non-tariff trade barriers vary strongly among sectors. The influence of the macroeconomic environment on MERCOSURś exports is examined in a dynamic panel analysis. A simulation study based on a quite comprehensive evaluation of EU trade barriers is performed for the Argentinean case in order to evaluate the impact of EU trade liberalisation.
Keywords: F13; F14; C23; 330; MERCOSUR-EU trade; trade barriers; sectoral study; panel data